Microwave-initiated rapid synthesis of phthalated cashew gum for drug delivery systems. (15th February 2021) - Oliveira, Antônia Carla de Jesus; Chaves, Luíse Lopes; Ribeiro, Fábio de Oliveira Silva; de Lima, Laís Ramos Monteiro; Oliveira, Thaisa Cardoso; García-Villén, Fátima; Viseras, César; de Paula, Regina C.M.; Rolim-Neto, Pedro José; Hallwass, Fernando; Silva-Filho, Edson C.; Alves da Silva, Durcilene; et al.
Graphical abstract: Highlights: Phthalated cashew gum was synthesized by the microwave-initiated method. 1 H NMR spectroscopy was used to assess the degree of substitution of phthalated cashew gum. Modified phthalated cashew gum nanoparticles were developed for delivery of benznidazole. Abstract: Chemical modification of polysaccharides is an important approach for their transformation into customized matrices that suit different applications. Microwave irradiation (MW) has been used to catalyze chemical reactions. This study developed a method of MW-initiated synthesis for the production of phthalated cashew gum (Phat-CG). The structural characteristics and physicochemical properties of the modified biopolymers were investigated by FTIR, GPC, 1 H NMR, relaxometry, elemental analysis, thermal analysis, XRD, degree of substitution, and solubility. Phat-CG was used as a matrix for drug delivery systems using benznidazole (BNZ) as a model drug. BNZ is used in the pharmacotherapy of Chagas disease. The nanoparticles were characterized by size, PDI, zeta potential, AFM, and in vitro release. The nanoparticles had a size of 288.8 nm, PDI of 0.27, and zeta potential of –31.8 mV. The results showed that Phat-CG has interesting and promising properties as a new alternative for improving the treatment of Chagas disease.